2020
DOI: 10.5116/ijme.5f50.bc76
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional versus uniprofessional dyad learning for medical students in a clinical setting

Abstract: Objectives: The aim of the present study was to explore and compare medical students' perceived learning outcomes when treating patients under supervision in two different learning settings: a uniprofessional or an interprofessional dyad. Methods: The design of the study is a qualitative interview study. Data were collected from October 2016 to June 2017 via semi-structured group interviews performed at the end of the clinical placement in an orthopaedic outpatient clinic for medical students in the last semes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…More recent studies have expanded upon this design by formulating interprofessional learning dyads, that is medical student–nursing student pairs. Preliminary research in the area has shown that working in interprofessional dyads helps medical students gain an awareness of their profession's strengths and weaknesses and can lead them to a more holistic understandings of treatment (Hansen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have expanded upon this design by formulating interprofessional learning dyads, that is medical student–nursing student pairs. Preliminary research in the area has shown that working in interprofessional dyads helps medical students gain an awareness of their profession's strengths and weaknesses and can lead them to a more holistic understandings of treatment (Hansen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 32 papers, seven explicitly mentioned the theoretical background on which the intervention was based. These included peer-assisted learning [30,36,59], Jeffries simulation theory [55], Bandura self-efficacy theory [46], Knowles's principles for Adult Learning as guidelines [53], goal theory perspective [59], model of inter-professionality, Beck's cognitive model, and social capital theory [56]. The remaining papers did not explicitly mention the theoretical background of the IPE program [29,[31][32][33][34][35][37][38][39][40][41][42][43][44][45][47][48][49][50][51][52]54,57,58,60].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies (n = 16) included students from two professions only [29,31,32,37,40,42,43,45,48,[52][53][54][55][56][57][58]. In addition to medical students, twenty-three studies included nursing, six papers included physiotherapy, four papers included pharmacology, and only two papers included psychology students (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We expect dyad learning and other group learning formats to be a part of tomorrow’s medical education system in both uni‐ and interprofessional formats due to growing student cohorts and an increasing team approach to patient care 16,26,27,49,56 . This provides new pedagogical challenges, but also potential for innovation of medical education in times of increasing productivity demands and medical personnel shortages.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have provided substantial evidence to support the effectiveness of dyad learning of clinical skills in the controlled simulated setting 1‐8 . Yet, despite these promising results, we identified few attempts in the published literature to examine the role of dyad learning as a method for training medical students in clinical clerkships 14‐16 . This may have to do with the fact that medical students' learning in the clinical setting depends on a complex interplay between doctors, nurses and patients.…”
Section: Introductionmentioning
confidence: 99%